PERAN LEMBAGA REHABILITASI DALAM PEMBINAAN MORAL PENGGUNA NAPZA DENGAN METODE THERAPEUTIC COMMUNITY (TC) SECARA SPIRITUAL DAN INTELEKTUAL - Dini Oktariani, - (2019)
Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pembinaan moral bagi korban penyalahgunaan napza, mengidentifikasi aktor pendukung dan penghambat dalam pelaksanaan pembinaan karakter, dan mengetahui upaya dalam mengatasi hambatan pemembinaan moral korban penyalahgunaan napza dengan metode Therapeutic Community (TC) di Balai Besar Rehabilitasi BNN. This research is a case study with a qualitative approach with research subjects, the head of the Rehabilitation Center of BNN, rehabilitation officers, and drug victims who are at the BNN Rehabilitation Center. Data is collected through interviews, observations, and documentation which is accompanied by a list of questions. All data collected is analyzed with an interpretation that is preceded by triangulation to determine the validity of the data. The findings of this study are: 1) Plans for spiritual and intellectual moral development for victims of drug abuse must be compiled comprehensively. This is because the TC Therapeutic Community Coaching program is a program that has a stay plan of 15 to 24 months. 2) The process of fostering spiritual and intellectual morals of victims of drug abuse through the Therapeutic Community method at the BNN Lido Rehabilitation Center is carried out through activities to improve aspects of knowledge, spiritual, moral, and ethical values. 3) The success of moral guidance at the BNN Lido Rehabilitation Center, when residents can cultivate spiritual and intellectual character using the Therapeutic Community method. 4) Constraints or obstacles experienced by the resident mostly come from their own personalities.